Strategi Kepala Madrasah Dalam Upaya Meningkatkan Prestasi Siswa Di MTS Unggulan Ponpes Amanatul Ummah Program Cerdas Istimewa Dan Excellent Pacet-Mojokerto - Asif, Ahmad; Zakariyah, Zakariyah; Prastiyo, Agus (Invention: Journal Research and Education Studies, 2023)
This study aims to describe the principal's strategy in an effort to increase religious values in MTs Amanatul Ummah Islamic Boarding School, Special Smart Program and Excellent Pacet-Mojokerto. This research uses a type of qualitative research with a descriptive approach. The object of this research was carried out at the Superior MTs of the Amanatul Ummah Islamic Boarding School, the Special Smart Program and the Excellent Pacet-Mojokerto. Data collection techniques use observation, interviews and documentation. Sources of data in this study included school principals, vice principals for the curriculum section, students and teachers. The analytical techniques used in this study are data collection, data reduction, data presentation, drawing conclusions. The triangulation used to test the validity of the data is source triangulation. The results of the study show that the principal's strategy is used to increase student achievement through inculcating religious values at PP Featured MTs. Amanatul Ummah Pacet is carried out in several aspects.